2017
DOI: 10.1080/03630269.2017.1337033
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Skin Color and Iron Levels in Pediatric Patients with β-Thalassemia Major Using a Visual Skin Color Chart

Abstract: Patients with β-thalassemia major (β-TM), a disease that emerges due to disorder of hemoglobin (Hb) synthesis, require life-long erythrocyte transfusion. The purpose of this study was to evaluate skin color and iron levels of patients with β-TM using a visual skin color chart. Each patient's skin color was matched on a skin color chart under a fluorescent lamp by the same physician on each occasion. Iron, iron binding capacity, ferritin and complete blood count (CBC) were studied for each patient enrolled. Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Spectrometry was used to confirm high iron deposition in the skin of patients with β-TM [ 32 ]. Bucak et al also revealed significant findings between the visual skin color chart (VSCC) and the iron parameters of β-TM patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectrometry was used to confirm high iron deposition in the skin of patients with β-TM [ 32 ]. Bucak et al also revealed significant findings between the visual skin color chart (VSCC) and the iron parameters of β-TM patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dermatological manifestations of patients with β-TM are darkened skin color and gingival hyperpigmentation due to iron overloading [ 5 ]. It is seen that there is a direct correlation between skin color and body iron levels in patients with β-TM [ 14 ]. Oral manifestations of thalassemia are malocclusion, high caries index, mucosal pallor, severe gingivitis, inflammation of salivary glands, thin mandibular cortex, multiple diastemas, spike-shaped and short roots, taurodontism, and dark-colored gingiva [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, age (p = 0.002) and the number of transfusions received yearly (p = 0.022) were shown to be associated with darker skin tones. Our review of the literature revealed no previous studies using a VSCC to evaluate skin color and iron values in people with β-thalassemia (30).…”
Section: Applications Of Atomic Absorption Spectroscopy To Analyze Bi...mentioning
confidence: 91%